An evaluation of bible and theological school libraries belonging to PABATS - Villareal, Ma. Nora A. 1968-
Findings revealed that PABATS librarians were responsible in formulating the library objectives. In terms of collection, librarians in Luzon, and Mindanao agreed to have adequate circulation and reference books while those in Visayas were undecided. As for the periodicals and non-book materials, all libraries were found to be weak. Perceptions in terms of policies, shelf-reading program, faculty participation and acquisition, libraries in Luzon and Mindanao rated well while those in Visayas showed slow progress. In the organization and access to materials, libraries in Luzon and Mindanao followed the necessary requirements while libraries in Visayas were found to be in need of improvements in the area of organizing and arranging of its collection and providing sufficient indexes to periodicals. The classification system used are the Dewey Decimal Classification (DDC) and the Library of Congress Classification Scheme (LCS). Staffing patterns in PABATS libraries showed that many of them have additional duties in ministerial work in their church and respective schools. Majority operate on a one-man library system.